THE EFFECT OF USING TONGUE TWISTER TO IMPROVE STUDENTS’ PRONUNCIATION MASTERY - Rizki Dwi Cahyani; Efrini Panjaitan (STKIP Budidaya Binjai, 2020)
This study aimed to find out whether using Tongue Twister to Improve Students’ Pronunciation Mastery at the Tenth Grade Students of SMA Swasta Melati Binjai In Academic Year 2019/2020. In this study, used Tongue Twister as the independent variable (X) and students’ pronunciation mastery as the dependent variable (Y), with the hypothesis: using Tongue Twister significantly affects students’ pronunciation mastery of the 2019/2020 tenth grade students of SMA Swasta Melati Binjai Senior High School. The population of this study was the 2019/2020 tenth grade students of SMA Swasta Melati Binjai Senior High School. Which consisted of 62 students. The sample was taken by using cluster random sampling, that consist of 62 students. Then, the sample was divided into two groups, the group taught by using Tongue Twister was as the experimental group and the group taught without Tongue Twister was as the control group. The writer used speaking test as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (t0) was higher than the value of t-table, (t-observed = 18.08 > t-table = 1.671). Therefore, the hypothesis proposed by the writer was accepted. In the other words, using Tongue Twister significantly affects the students’ pronunciation mastery of the 2019/2020 tenth grade students at SMA Swasta Melati Binjai Senior HighSchool.